The elements of executive attention in top soccer referees and assistant referees - Pietraszewski, P.; Roczniok, R.; Maszczyk, A.; Grycmann, P.; Roleder, T.; Stanula, A.; Fidos-Czuba, O.; Ponczek, M. (Journal of Human Kinetics, 2014)
The aim of the present study was to compare executive attention of top soccer referees and assistant referees at different levels of professional attainment. The sample consisted of 53 subjects (FIFA and national level) - 30 referees and 23 assistant referees. Executive attention of assistant referees was significantly better than the referees` (p<0.01). Furthermore, extraclass and international referees demonstrated better executive attention than the first-league referees (p<0.01). The research results have proved that referees` executive attention differs depending on their function and professional level, as well as indicated that the quality of abilities may influence the number and correctness of decisions made during a game. This elementary cognitive process may be strongly shaped by individual`s experience and age. This finding may be instrumental in screening referees and developing criteria for recruiting future referees.